1994
DOI: 10.1111/j.1365-2583.1994.tb00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal mapping of two loci affecting filarial worm susceptibility in Aedes aegypti

Abstract: Two quantitative trait loci (QTL) affecting susceptibility of the mosquito Aedes aegypti to the filarial worm parasite Brugia malayi were identified using restriction fragment length polymorphism (RFLP) markers. The first locus, fsb[1,LF178], resides within a 10 cM interval on chromosome 1 and exhibits a recessive effect with respect to susceptibility. The second locus, fsb[2,LF98], resides within a 9 cM interval on chromosome 2 and exhibits an additive effect on susceptibility. Significant epistasis was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 31 publications
2
48
0
Order By: Relevance
“…One of the primary goals of quantitative genetics is to estimate the extent to which variation in a trait (phenotypic variance, V P ) is conditioned by the environment (environmental variance, V E ) and genetics (genetic variance, V G ). The genetic variance is further partitioned into additive genetic variance (V A ) and dominance variance (V D ) to differentiate between alleles at a locus that act additively versus those that are dominant to other alleles.Given that vector competence is under polygenic control [15][16][17] and significantly influenced by environmental effects, vector competence is appropriately analyzed as a quantitative trait. One of the most measured quantitative genetic parameters is the narrow-sense or additive genetic heritability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the primary goals of quantitative genetics is to estimate the extent to which variation in a trait (phenotypic variance, V P ) is conditioned by the environment (environmental variance, V E ) and genetics (genetic variance, V G ). The genetic variance is further partitioned into additive genetic variance (V A ) and dominance variance (V D ) to differentiate between alleles at a locus that act additively versus those that are dominant to other alleles.Given that vector competence is under polygenic control [15][16][17] and significantly influenced by environmental effects, vector competence is appropriately analyzed as a quantitative trait. One of the most measured quantitative genetic parameters is the narrow-sense or additive genetic heritability.…”
mentioning
confidence: 99%
“…Given that vector competence is under polygenic control [15][16][17] and significantly influenced by environmental effects, vector competence is appropriately analyzed as a quantitative trait. One of the most measured quantitative genetic parameters is the narrow-sense or additive genetic heritability.…”
mentioning
confidence: 99%
“…The first such study evaluated the genetic control of susceptibility of A. aegypti to infection with the human pathogen B. malayi (212). Results from crosses involving three separate populations revealed linkage associations between parasite susceptibility and cDNA markers at two loci.…”
Section: Genetic Basis Of Vector Competencementioning
confidence: 99%
“…Results from crosses involving three separate populations revealed linkage associations between parasite susceptibility and cDNA markers at two loci. Susceptibility seems to be controlled by a QTL on chromosome 1 (fsb [1,LF178]) that functions as a recessive allele (verifying the location and characteristics of f m ) and a QTL on chromosome 2 (fsb [2,LF98]) that exerts an effect on fsb [1,LF178] in an additive manner (212). Subsequently, QTL mapping of the susceptibility of A. aegypti to the avian malaria parasite P. gallinaceum revealed that, again, the dual action of two QTL influenced the phenotypic trait of parasite susceptibility (213).…”
Section: Genetic Basis Of Vector Competencementioning
confidence: 99%
“…A physical map for Ae. aegypti corresponding to 13.3% of the genome was developed using FISH markers on mitotic chromosomes (Severson et al, 1993), genetic linked map (RFLP cDNA-based map) (Brown et al, 1995(Brown et al, , 2001Sharakhova et al, 2011), and QTL (Severson et al, 1994(Severson et al, , 1995Bosio, Fulton and Salasek, 2000;Gomez-Machorro, Bennett and Muñoz, 2004;Zhong et al, 2006). More recently, a more detailed physical map of the mosquito was constructed and a total of 624 Mb covered approximately 45% of the Ae.…”
Section: │ 3 Genetics Of the Mosquito Ae Aegypti Safety Assessmentomentioning
confidence: 99%